A taxonomic summary of Aphelidiaceae - Peter M. Letcher; Martha J. Powell (IMA Fungus)
Abstract Aphelids are parasitoids of various algae and diatoms, and in a recent classification are contained in family Aphelidiaceae, phylum Aphelidiomycota, kingdom Fungi. Family Aphelidiaceae (the only family in the phylum) is composed of four genera: Aphelidium, Paraphelidium, Amoeboaphelidium, and Pseudaphelidium. All species are known morphologically, and most have been illustrated. Few have been examined ultrastructurally, and even fewer have been sequenced for molecular comparisons. Recent studies in molecular phylogenetics have revealed an abundance of related environmental sequences that indicate unrealized biodiversity within the group. Herein, we briefly summarize the history of aphelids and acknowledge the controversy of placement of the group with related organisms. With light microscopic images and transmission electron micrographs, we illustrate typical life cycle stages for aphelids, provide updated descriptions and taxonomy for all described species, and provide a key to the species.